Numerical quantification of aerodynamic damping on pitching of vehicle-inspired bluff body - Cheng, S.Y.; Tsubokura, M.; Nakashima, T.; Okada, Y.; Nouzawa, T. (Journal of fluids and structures, 2012)
The influence of transient flows on vehicle stability was investigated by large eddy simulation. To consider the dynamic response of a vehicle to real-life transient aerodynamics, a dimensionless parameter that quantifies the amount of aerodynamic damping for vehicle subjects to pitching oscillation is proposed. Two vehicle models with different stability characteristics were created to verify the parameter. For idealized notchback models, underbody has the highest contribution to the total aerodynamic damping, which was up to 69%. However, the difference between the aerodynamic damping of models with distinct A- and C-pillar configurations mainly depends on the trunk-deck contribution. Comparison between dynamically obtained phase-averaged pitching moment with quasi-steady values shows totally different aerodynamic behaviors. ► We introduce a coefficient to quantify the aerodynamic damping for road vehicle. ► Underbody has the highest contribution to the total aerodynamic damping. ► Difference in aerodynamic damping of vehicles depends on the trunk-deck contribution.